TNK-tPA for Acute Myocardial Infarction: The Clinical Experience - Pislaru, Sorin V.; Van de Werf, Frans (Thrombosis and Haemostasis, 1999)
Thrombolytic therapy has become the mainstay of treatment for acute transmural myocardial infarction. Present fibrinolytic regimens have a number of shortcomings, including the failure to induce early and sustained reperfusion in as many as 40-50% of the patients, and to prevent reocclusion in another 10-20% of the patients. The efforts for improving thrombolysis are focused on the development of new agents (fibrinolytics, anticoagulants, and antiplatelet agents). TNK-tPA is a triple combination mutant of wild-type tissue plasminogen activator that exhibits a longer plasma half-life, an enhanced fibrin-specificity, and an increased resistance to the plasminogen activator inhibitor-1. This paper summarizes the results of clinical trials with TNK-tPA in acute myocardial infarction.
Keywords: Thrombolysis; TNK-tPA; acute myocardial infarction